Third Åland islands conference on von Willebrand disease, 26–28 September 2012: meeting report. (6th February 2013) - Berntorp, E.; Fuchs, B.; Makris, M.; Montgomery, R.; Flood, V.; O'Donnell, J. S.; Federici, A. B.; Lillicrap, D.; James, P.; Budde, U.; Morfini, M.; Petrini, P.; et al.
Summary: The first meeting of international specialists in the field of von Willebrand disease (VWD) was held in the Åland islands in 1998 where Erik von Willebrand had first observed a bleeding disorder in some members of a family from Föglö and a summary of the meeting was published in 1999. The second meeting was held in 2010 and a report of the meeting was published in 2012. Topics covered included progress in understanding of VWD over the last 50 years; multimers; classification of VWD; pharmacokinetics and laboratory assays; genetics; treating the paediatric patient; prophylaxis; geriatrics; gene therapy and treatment guidelines. This third meeting held over 3 days covered the structure and function of von Willebrand factor (VWF); type 1 VWD, the most common form of the disease; a lifespan of pharmacokinetics in VWD; detecting inhibitors in VWD patients; and special challenges in understanding and treating the female VWD patient.